Examining Islamic Economic Thought: Adiwarman Azwar Karim - Muhammad Fadel; Muslimin Kara; Rahman Ambo Masse; Nurjannah Nurjannah (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Manado, 2023)
Adiwarman Azwar Karim is one of the contemporary Muslim scholars in Indonesia who has an important role in the development of Islamic economics in Indonesia. His thoughts and ideas gave birth to various works that became a reference for academics and practitioners of Islamic economics so that it had a major impact on the development of Islamic economics today. The purpose of this research is to look at some of Adiwarman Azwar Karim's thoughts. The method used is a literature study with a descriptive qualitative approach. Data sources come from secondary data sources, namely journals and books related to the discussion. The results showed that the methods and approaches used by Adiwarman Karim in his various works were historical approaches, fiqh and economic approaches. Some of Adiwarman Karim's economic thoughts are Islamic Economic Design, Intellectual Integration and Harakah; Campus-Government-Practitioner, Mudharabah Concept, Gold Pawn and Economic Value of Time. In addition, Adiwarman avoids Islamizing the economy by taking conventional economics and then tracing the verses of the Qur'an and hadith because it forces the Qur'an and hadith to match the human mind.